Arktiske diskurser - mennesket i Arktis - Henning Howlid Wærp (Nordlit: Tidsskrift i litteratur og kultur, 2014)
The article discusses the definition of the Arctic in Norway – by asking questions like ´where is the Arctic, what is the Arctic´ – and by investigate extracts from literature and politics, travelogues and tourism. The author shows that there are multiple definitions of the Arctic, and that many of them are connected to certain interests.